Influence Analysis of Transmission Lines on a Stable Non-Foster-Loaded Electrically Small Dipole - Zhixun Huang; Hu Yang; Taolin Liu (International Journal of Antennas and Propagation)
Non-Foster-loaded antennas have the advantages of compact size and large bandwidth. Meanwhile, they suffer from two issues: internal instability and simulation inaccuracy resulting from distribution parameters. The most commonly used stability analysis method for microwave circuits, Rollett’s criteria, is not suitable for negative impedance circuits. This paper has explained the reason and proposed an effective method for stability analysis. Transmission lines between lumped components are found to be a main reason of inaccurate simulations, which is analyzed in this paper, and it is concluded that their influence also exists at hundreds of megahertz. In order to solve this problem and improve simulation accuracy, circuit and electromagnetic cosimulation is conducted. Finally, a 320 mm dipole loading with a negative capacitor is fabricated to verify the analysis. Simulated and measured results indicate that the proposed stability analysis is effective and the simulation accuracy is significantly improved. The matched dipole achieves less than −10 dB reflection coefficient from 30 MHz to 580 MHz. Furthermore, a 14 dB gain improvement is obtained in electrically small condition.